Copper |Oxide (Cu_2 O) Sheet Based Solar Cell (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background:Copper oxide  is a potential material for the fabrication of low cost solar cells for terrestrial application. It is one of the earliest semiconductor materials investigated for solar cells in the early century. Copper oxide exists in forms of  with a certain band gap, which is at room temperature.  A copper sheet has been used to create a solar cell that would use the sun's energy to produce electricity. The copper oxide is an ancient solar cell that converts sunlight into current in which a photon is turned into an electric signal, it is known as photovoltaic. Photovoltaic cell is an electrical device that converts the energy of light directly into electricity by the photovoltaic effect. Materials and Methods:We conducted our experiment using pure water first, followed by salt water, and compared the outcomes. The salt (Nacl) solution was added to water, the solution acts as an electrolyte. We found that salt water was a superior electrolyte after analyzing the data.Results:As a result, we utilized a sodium chloride (Nacl) solution as the cell's salt water electrolyte. On the other hand, differing electrolyte concentrations and light intensity were significant considerations that both demonstrated their own roles in solar cell.Conclusion:This project's purpose was to produce alternate solar cells made from cheap materials and easiest designed that could serve as a model for a new solar cell. It consists of Copper Oxide along with salt water (Nacl) solution.